The Concept of Teaching and its Essential questions - Nematolah Mousapour (Kerman University of Medical Sciences, 2004)
Teaching is an interpersonal activity an interaction based on the verbal communication which is inclined to learning or change of behavioral methods in one or more students and it is considered as a Process Although some essential specifications such as process interaction intention are involved answering to the following three essential questions seems not to be easy: 1 What is Teaching? 2 Who are Participating in a Teaching Activity? 3 What is the role of each person in a Teaching Activity? These questions have different answers though they would provide a base for gathering and inclining of researches and theories The first question reveals the type of activity as either a Science or an Art The second question is a discussion about teacher and student and description of both Answering to the third question is pointing to the role of the Teacher and Student who are active or non active and different methods of teaching are based on it